Peacebuilding and NGOs : state-civil society interactions - Christie, Ryerson (Routledge studies in peace and conflict resolution., 2013)
Analysing the relationship between civil society and the state, this book lays bare the assumptions informing peacebuilding practices and demonstrates through empirical research how such practices have led to new dynamics of conflict. The drive to establish a sustainable liberal peace largely escapes critical examination. When such attention is paid to peacebuilding practices, scholars tend to concentrate either on the military components of the mission or on the liberal economic reforms. This means that the roles of Non-Governmental Organizations (NGOs) and the impact of attempting t.